Horses : how to choose and care for a horse - Jeffrey, Laura S. (Berkeley Heights, N.J., U.S.A. : Enslow Publishers, 2004)
Provides information on owning a horse, including how to choose among different breeds and how to groom, house, feed, and keep a horse healthy.
Includes bibliographical references (p. 47) and index.
Accelerated Reader AR
Keywords: Horses -- Juvenile literature; Horsemanship -- Juvenile literature; Horses; Pets